1991
DOI: 10.3928/0147-7447-19910501-09
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal Morphine: Dosage and Efficacy in Younger Patients for Control of Postoperative Pain Following Spinal Fusion

Abstract: Intrathecal morphine in an average dose of 0.01 mg/kg was given to 33 patients between ages 11 and 16 years who had spinal arthrodesis for idiopathic scoliosis. The morphine was administered intrathecally as a 10-cc bolus at the conclusion of the arthrodesis, but before closure. The goal was to study safety in terms of respiratory depression and pain relief Respirations occurred spontaneously in 30 of the 33 patients within 15 minutes of cessation of anesthesia. Respiratory depression occurred in five patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…any PONV-lowering strategy by reducing opioid consumption through modifying administration techniques, altering routes of administration, and adjusting dosing regimens reported 22,23,28,29,35,73,74 . However, we noted a trend toward lower PONV rates when epidural analgesic methods were used without combination 28,75 , lower opioid dose administration 25,27,28,76 , and with subcutaneous/epidural analgesic route [75][76][77] . Nonpharmacological measures such as the use of chewing gum has shown to reduce PONV in laparoscopic or breast surgery 78 .…”
Section: Discussionmentioning
confidence: 83%
“…any PONV-lowering strategy by reducing opioid consumption through modifying administration techniques, altering routes of administration, and adjusting dosing regimens reported 22,23,28,29,35,73,74 . However, we noted a trend toward lower PONV rates when epidural analgesic methods were used without combination 28,75 , lower opioid dose administration 25,27,28,76 , and with subcutaneous/epidural analgesic route [75][76][77] . Nonpharmacological measures such as the use of chewing gum has shown to reduce PONV in laparoscopic or breast surgery 78 .…”
Section: Discussionmentioning
confidence: 83%
“…Milbrandt et al [11] performed a retrospective study comparing PCA, EPI and IM for pain management in patients with adolescent idiopathic scoliosis undergoing PSF and found all three to be well-tolerated, although transient neurologic changes were seen in 20% of patients in the EPI group. While numerous studies have shown IM to be effective and well-tolerated in patients with adolescent idiopathic scoliosis undergoing PSF and SSI, none of these have examined the use of IM in children with EOS undergoing initial growing rod instrumentation or final fusion [5][6][7][8][9][10][11][12][13][14][15]. The purpose of this study was to determine if a single preincision dose of IM can be used in a well-tolerated and effective manner for postoperative pain control in patients with EOS undergoing initial instrumentation and final PSF and SSI.…”
Section: Discussionmentioning
confidence: 99%
“…There is variation in the dosing of intrathecal morphine for spine surgery in children, ranging from 2 to 20 mcg/kg in published reports [5][6][7][8][9][10][11][12][13]15]. We have used a dose of 9-19 mcg/kg up to 1 mg through the full duration of the study period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation